Standard- und Modulbasierte digitale Rohbauprozesskette : Frühzeitige Produktbeeinflussung bezüglich Produktionsanforderungen im Karosserierohbau der Automobilindustrie - Walla, Waldemar (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Karlsruher Institut für Technologie, Institut für Informationsmanagement im Ingenieurwesen (IMI), 2017)
Standardization and modularization offers big advantages not only for the product development but also for production and planning departments. But industry often doesn't utilize these advantages. This contribution introduces a new method which supports the developer to design a new product in order to fit to the standardized and modularized production.